Cotillion Dance as an Embodiment of Class. (2014) - Blacker, C. Alexandra
Abstract : This paper suggests that social dance, specifically cotillion, teaches students to internalize and reflect ideas relevant to constructions of class. An examination of eighteenth- and nineteenth-century cotillion dance (also referred to as private balls, public balls, assemblies, and dance halls) shows a physical manifestation of class that can still be seen in the modern day dance world. This paper examines social dance in the eighteenth and nineteenth centuries. I use historical references, specifically Elizabeth Aldrich's From the Ballroom to Hell: Grace and Folly in Nineteenth-Century Dance, Linda Tomko's Dancing Class, Gender, Ethnicity, and Social Divides in American Dance, and the Library of Congress Web site to foreground this idea before turning to some modern day case studies. Employing historical as well as interview-based methodologies, the paper combines interviews from present day cotillion directors with my own experiences in the cotillion and professional ballet communities. The paper concludes that social dance in the eighteenth and nineteenth centuries sets up a tradition still carried forth today—one that is more about classed aspirations and courtship and less about dance technique or physical ability.